Catholic religious elements in the university ceremonyNadie cuestiona, a estas alturas del siglo XXI, que la Universidad es una invención de la Iglesia católica. Con el fin de formar a sus futuros monjes, fruto del auge que surge en la vida monástica, a p (Journal of the Sociology and Theory of Religion, 2020)
No one questions, at this point in the 21st century, that the University was an invention of the Catholic Church. In the 9th century, the future monks attended the schools inside the monasteries, given the rise of monastic vocations. Simultaneously, clergymen, whose education happened in the cathedrals since the 11th century, in the so called episcopal schools (we know this fact thanks to the documents and manuscripts treasured in their libraries), will also depend on the Studium Generale (general study) and the universities from the 13th century onwards (which, in turn, will verify the academic formation of the clergy in the different cathedral cabildos).The ecclesiastical imprint (the "Catholic Church" mark) when it comes to teaching, included certain elements during lliturgy and university ceremonies, which have remained unchanged in Christianity. Despite the secularization of Spanish university (almost definitive in the 19th century), many Catholic elements have remained part of its academic ceremonial, at the core of its tradition, and they are considered to be a significant aspect of the academic institution: gestures, costumes, colors and, thus, the Catholic Church’s rituals, among others, are part of these elements nowadays
Keywords: Influence University Church; Catholic academic events; religious university ceremonial.